2011
DOI: 10.1523/jneurosci.1902-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Control of Attention by Stimulating Mesolimbic-Corticopetal Cholinergic Circuitry

Abstract: Sustaining and recovering attentional performance requires interactions between the brain’s motivation and attention systems. The first experiment demonstrated that in rats performing a sustained attention task (SAT), presentation of a distractor (dSAT) augmented performance-associated increases in cholinergic neurotransmission in prefrontal cortex (PFC). Because stimulation of NMDA receptors in the shell of the nucleus accumbens (NAC) activates PFC cholinergic neurotransmission, a second experiment demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(185 citation statements)
references
References 73 publications
(89 reference statements)
7
167
1
Order By: Relevance
“…Intra-NAC NMDA administration facilitates attentional performance under conditions of enhanced demands on performance, suggesting that NAC-cholinergic interactions mediate the motivated recruitment of attention systems (St Peters et al, 2011). This evidence is consistent with the hypothesis that stimulation of NAC NMDA receptors mimics the top-down PFC-NAC activation of the BFCS, an activation that is critical for the recruitment of motivation to stay on task when faced with enhanced cognitive load.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Intra-NAC NMDA administration facilitates attentional performance under conditions of enhanced demands on performance, suggesting that NAC-cholinergic interactions mediate the motivated recruitment of attention systems (St Peters et al, 2011). This evidence is consistent with the hypothesis that stimulation of NAC NMDA receptors mimics the top-down PFC-NAC activation of the BFCS, an activation that is critical for the recruitment of motivation to stay on task when faced with enhanced cognitive load.…”
Section: Introductionsupporting
confidence: 82%
“…In intact animals, perfusion of NMDA into the NAC shell markedly stimulates basal ACh levels in PFC (Zmarowski et al, 2005), and this NMDA modulation is facilitated by concurrent activation of D1 receptors in NAC (Zmarowski et al, 2005) and inhibited by stimulation of D2 receptors (Brooks et al, 2007). Recently, we demonstrated that infusions of NMDA into NAC shell rescued the falling performance of rats performing in a sustained attention task when faced with distractors that otherwise severely impair attentional processing (St Peters et al, 2011). Thus, NMDA-mediated elevation of prefrontal ACh levels serves as a bioassay for testing the integrity and efficacy of topdown control mechanisms that are essential for maintaining goal-directed behavior.…”
Section: The Validity Of the Vh Ttx Inactivation Model For Szmentioning
confidence: 98%
“…Our current circuitry model suggests that separate cholinergic neuromodulatory activity, acting on a scale of minutes, can influence the generation of transients via stimulation of nicotinic ACh receptors expressed by thalamic glutamatergic terminals (37,38). Cholinergic neuromodulation varies as a function of levels of top-down attentional control and is driven in part by mesolimbic activity (39). This hypothesis predicts that the loss of reward caused by distractors and associated error rates alters the likelihood for, and perhaps also the dynamics of, cholinergic transients.…”
Section: Discussionmentioning
confidence: 98%
“…This dysregulation may contribute to the performance deficits in the task given the significant role that cortical cholinergic transmission has in attentional processing (Hasselmo and Sarter, 2011;Sarter et al, 2005) and, more specifically, the importance of the mesolimbic recruitment of prefrontal ACh release to maintain performance as the conditions of the task become more challenging (St Peters et al, 2011). Finally, in a series of studies using infusions of TTX into VH at PD7, Louilot and colleagues have reported abnormalities in accumbens dopaminergic transmission related to deficits in performance in a latent inhibition task (Meyer et al, 2009;Peterschmitt et al, 2008).…”
Section: Potential Mechanisms Contributing To Set-shifting Deficitsmentioning
confidence: 99%
“…Through integration of these inputs, the NAC influences PFC activation by various pathways, including direct modulation from the basal forebrain cortical cholinergic system (BFCS; Zaborszky and Cullinan, 1992). We previously demonstrated that glutamatergic excitation of the NAC can evoke acetylcholine (ACh) release in the PFC (Zmarowski et al, 2005;Brooks et al, 2007), thereby recruiting interactions between motivational and attentional mechanisms necessary to ensure stable attentional performance when demands on cognitive control are high (St Peters et al, 2011).…”
Section: Introductionmentioning
confidence: 99%